ANALISA KEKUATAN DAN DEFORMASI MENGGUNAKAN METODE ELEMEN HINGGA (FEM) PADA KEKUATAN PALLET - Doni Kurniawan; Angga Nugraha; Raja Muhammad Yusli Hardika; Zakwan Hilmy (JURNAL JALASENA, 2023)
FEM is an analytical method that uses a numerical approach. In FEM, the structure to be analyzed is discretized into small elements (with a calculated number) where each element is connected to a nodal point or discrete point. The use of FEM has been widely carried out in the world of engineers where the analysis process is carried out by analyzing the model of an object using Computer Aided Engineer (CAE) software. Pallet is a tool in the logistics transportation process. Pallet functions as a base for goods in the storage process. Therefore, this research discusses FEM analysis using CAE on the pallet model to see the Normal Stress, Deformation, and Equivalent Stress that occurs when the pallet is given a load. The result of this research is that the Normal Stress that occurs is not significant. Deformation occurs at the ends of the pallet supports.